ENDOMETRIOMA COEXISTING WITH MATURE CYSTIC TERATOMA IN A SINGLE OVARY: A RARE PRESENTATION - Fatima Shams; Ahmed, Shahroze; Mudasira Habib; Abdul Sattar Anjum (Journal of Ayub Medical College Abbottabad, 2024)
Mature cystic teratomas, commonly known as dermoid cysts, are prevalent benign ovarian tumors that originate from germ cells and mature into diverse tissue types. They are usually asymptomatic but can lead to complications like torsion, rupture, or malignant transformation. Endometriosis is a condition in which endometrial tissue grows outside the uterus and it is commonly associated with pelvic pain and infertility. We report a case of a 27-year-old woman who presented with a history of lower abdominal pain and dysmenorrhea. Initial ultrasonography revealed a complex cyst in the left ovary which, on a later Magnetic Resonance Imaging (MRI) scan, proved to be two distinct cystic lesions within the same ovary. Subsequently, a laparatomy and ovarian resection was done, and histopathologic examination confirmed the coexistence of a mature cystic teratoma and an endometrioma in the left ovary. This case report highlights the unique occurence of these two conditions simultaneously, the challenges of differentiating these coexisting conditions and emphasizes the importance of utilizing multiple imaging modalities to achieve an accurate pre-operative diagnosis.